A Kinematic Study of Prosodic Structure in Articulatory and Manual Gestures: Results from a Novel Method of Data Collection. Issue 1 (13th March 2017) - Krivokapić, Jelena; Tiede, Mark K.; Tyrone, Martha E.
Abstract : The primary goal of this work is to examine prosodic structure as expressed concurrently through articulatory and manual gestures. Specifically, we investigated the effects of phrase-level prominence (Experiment 1) and of prosodic boundaries (Experiments 2 and 3) on the kinematic properties of oral constriction and manual gestures. The hypothesis guiding this work is that prosodic structure will be similarly expressed in both modalities. To test this, we have developed a novel method of data collection that simultaneously records speech audio, vocal tract gestures (using electromagnetic articulometry) and manual gestures (using motion capture). This method allows us, for the first time, to investigate kinematic properties of body movement and vocal tract gestures simultaneously, which in turn allows us to examine the relationship between speech and body gestures with great precision. A second goal of the paper is thus to establish the validity of this method. Results from two speakers show that manual and oral gestures lengthen under prominence and at prosodic boundaries, indicating that the effects of prosodic structure extend beyond the vocal tract to include body movement.1